Soft skills for everyone - Jeft Butterfield (cenage Learning, 2012)
Give your students a 360 degree education and a career advantage with Soft Skills for Everyone. This text delves into the most sought-after skills in the professional world, making students more marketable to employers. Covering topics such as being a team leader and working in groups, developing a personal work ethic and planning and managing a career, this streamlined book presents essential information on a topic once considered unable to be taught within the classroom.